Economic development, integration, and morality in Asia and the Americas - Wood, Donald C. (Research in economic anthropology, 2009)
This 29th volume in the Research in Economic Anthropology series explores economic development, integration, and morality in economic transactions in Asia and the Americas through 14 original chapters based on ethnographic evidence collected by the authors. Under development, chapters look at, amongst others, underground gambling behavior in China in light of that country's current economic boom, recent retail store expansion and local socioeconomic effects in rural Mexico, and also women's economic activities as part of the household economy in Oaxaca, Mexico. As for economic integration, authors investigate monetization in the historical and archaeological records of the Angkorian Empire, transnational economic links between coffee producers in Costa Rica and Panama and concurrent socio-economic effects at the production sites. Finally, under the moral, chapters examine the culture of restaurant tipping in North America, the pre-school education market in northern Japan against a backdrop of scarcity of children, narrative and social pressure in a North American market environment, and the role of social capital in gender-specific credit association membership in Puebla, Mexico.